GEOLOGI BAWAH PERMUKAAN DESA HUIDU MELITO, KECAMATAN TOMILITO, KABUPATEN GORONTALO UTARA, PROVINSI GORONTALO - Abduh, Alan Gani; Zainuri, Ahmad; Akase, Noviar (Universitas Negeri Makassar, 2024)
The research location is in Huidu Village, Tomilito District, North Gorontalo Regency, Gorontalo Province. The purpose of this study is to determine the geological conditions in the research area (Huidu Melito Village, Tomilito District) and analyze the cross-section of subsurface geology of the 2D model of the research area. The research methods carried out include surface data retrieval, subsurface data retrieval, and drill data retrieval. Analysis stages such as petrology, geoelectric analysis and drill sample analysis. The results obtained Geomorphology of the research area are in the form of Denudational Plain Units and Alluvial Plain Units. Stratigraphy in the study area is arranged from old to young age in the form of andesite units, volcanic breccia units and alluvial deposit units. Based on surface geology and subsurface geoelectric surveys, subsurface lithology of the study area consists of 6 rock layers including the first layer in the form of Top Soil, the second layer is the Breccia layer, the third layer is the Sand layer (Aquifer), the fourth layer is the Breccia layer, the fifth layer is the Andesite layer, the sixth layer is the Sand layer (Aquifer).